Sustainability of Bhutan's Hydropower (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Bhutan’s river potential for hydropower has been estimated at ~30,000 MW, the majority of which is concentrated in the Wangchhu, Punatsangchhu, Mangdechhu and Drangmechhu river basins. Hydropower forms the backbone of Bhutan’s socio-economic strength: Ninety nine percentage of its electricity supply comes from hydropower generation and hydropower alone contributes of national revenue. Bhutan has been cast as a model in South Asia for its environmental conservation policy. However, the impacts of climate change are becoming evident in the form of fast-retreating glaciers and erratic precipitation patterns that will prove to be costly for the hydropower sector as the country continues to bank on this renewable natural resource.DOI: http://dx.doi.org/10.3126/hn.v14i0.11272 HYDRO Nepal JournalJournal of Water, Energy and EnvironmentVolume: 14, 2014, JanuaryPage: 73-76